Adolescence and information and communication technologies. A challenge for the current Cuban society - Grettel Águila Calero; José Aurelio Díaz Quiñones; Paula Maribel Díaz Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Adolescence as a stage of development is a period where it is possible to enrich knowledge with the new technologies of information and communication, but it also represents risks for physical and mental health. In this work, it is discussed about the health problem that the inadequate management the new technologies of Information and communication could represent for our adolescents and positive parenting main role in facing this reality so as the needs of knowledge on the parents part to manage adequately this significant technological development.